Biosensors in Drug Discovery and Drug Analysis - Aydin, Elif B.; Aydin, Muhammet; Sezginturk, Mustafa Kemal (Current Analytical Chemistry, 2019)
Background: The determination of drugs in pharmaceutical formulations and human biologic fluids is important for pharmaceutical and medical sciences. Successful analysis requires low sensitivity, high selectivity and minimum interference effects. Current analytical methods can detect drugs at very low levels but these methods require long sample preparation steps, extraction prior to analysis, highly trained technical staff and high-cost instruments. Biosensors offer several advantages such as short analysis time, high sensitivity, real-time analysis, low-cost instruments, and short pretreatment steps over traditional techniques. Biosensors allow quantification not only of the active component in pharmaceutical formulations, but also the degradation products and metabolites in biological fluids. The present review gives comprehensive information on the application of biosensors for drug discovery and analysis. Moreover, this review focuses on the fabrication of these biosensors. Methods: Biosensors can be classified as the utilized bioreceptor and the signal transduction mechanism. The classification based on signal transductions includes electrochemical optical, thermal or acoustic. Electrochemical and optic transducers are mostly utilized transducers used for drug analysis. There are many biological recognition elements, such as enzymes, antibodies, cells that have been used in fabricating of biosensors. Aptamers and antibodies are the most widely used recognition elements for the screening of the drugs. Electrochemical sensors and biosensors have several advantages such as low detection limits, a wide linear response range, good stability and reproducibility. Optical biosensors have several advantages such as direct, real-time and label-free detection of many biological and chemical substances, high specificity, sensitivity, small size and low cost. Modified electrodes enhance sensitivity of the electrodes to develop a new biosensor with desired features. Chemically modified electrodes have gained attention in drug analysis owing to low background current, wide potential window range, simple surface renewal, low detection limit and low cost. Modified electrodes produced by modifying of a solid surface electrode via different materials (carbonaceous materials, metal nanoparticles, polymer, biomolecules) immobilization. Recent advances in nanotechnology offer opportunities to design and construct biosensors. Unique features of nanomaterials provide many advantages in the fabrication of biosensors. Nanomaterials have controllable chemical structures, large surface to volume ratios, functional groups on their surface. To develop proteininorganic hybrid nanomaterials, four preparation methods have been used. These methods are immobilization, conjugation, crosslinking and self-assembly. In the present manuscript, applications of different biosensors, fabricated by using several materials, for drug analysis are reviewed. The biosensing strategies are investigated and discussed in detail. Results: Several analytical techniques such as chromatography, spectroscopy, radiometry, immunoassays and electrochemistry have been used for drug analysis and quantification. Methods based on chromatography require timeconsuming procedure, long sample-preparation steps, expensive instruments and trained staff. Compared to chromatographic methods, immunoassays have simple protocols and lower cost. Electrochemical measurements have many advantages over traditional chemical analyses and give information about drug quantity, metabolic fate of drugs, and pharmacological activity. Moreover, the electroanalytical methods are useful to determine drugs sensitively and selectivity. Additionally, these methods decrease analysis cost and require low-cost instruments and simple sample pretreatment steps. Conclusion: In recent years, drug analyses are performed using traditional techniques. These techniques have a good detection limit, but they have some limitations such as long analysis time, expensive device and experienced personnel requirement. Increased demand for practical and low-cost analytical techniques biosensor has gained interest for drug determinations in medical sciences. Biosensors are unique and successful devices when compared to traditional techniques. For drug determination, different electrode modification materials and different biorecognition elements are used for biosensor construction. Several biosensor construction strategies have been developed to enhance the biosensor performance. With the considerable progress in electrode surface modification, promotes the selectivity of the biosensor, decreases the production cost and provides miniaturization. In the next years, advances in technology will provide low cost, sensitive, selective biosensors for drug analysis in drug formulations and biological samples.
Keywords: biosensors